Lecturer E-learning Training: The Role of Social Exchange Theory - Sulistyan, Riza Bahtiar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
The existence of the Covid-19 pandemic is able to change the organizational system that is already running normally. These changes have a profound impact on the human resources of the organization for security reasons. Not all organizations are ready to accept these changes, so there needs to be a special system that is used to keep the organization running normally. With reference to the development of social exchange theory, that training can improve the abilities of employees and the positive results will return to the organization. In this case there is a social exchange between the organization and its human resources. The impact of covid-19 is also felt at the tertiary level in Indonesia. The method used is the preparation, implementation, and evaluation stages. The participants of this training are all lecturers of STIE Widya Gama Lumajang, East Java. The training results show that there is an increase in ability before and after training. Organizations are not worried about changes in the method of the online learning system that has been established.